The Prisons of Democracy: Experiences of Prison Management in Contemporary Argentina - Lombraña, Andrea Natalia (2023)
The article presents a set of dissimilar experiences and a diversity of state responses in prison matters since the recovery of democracy in Argentina based on the identification of three relevant moments. The first is marked by the search for a politically progressive public policy and a democratic penitentiary practice (1983–1989); the second, by the design and implementation of the “Plan Director de la Política Penitenciaria Argentina” (Master plan for Argentine prison policy), aimed at the recovery of the correctionalist model and its institutional consolidation (1990–1999); and the third was sustained by an abrupt change of course embodied in the Sentencing Plan, following the models of “risk”, the desistance from crime and the Anglo-Saxon criminologies of “What Works” (2014–2020).